The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1123/jis.2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Student-Athletes’ Contentment With Academic Services

Abstract: The purpose of this study sought to investigate factors that influence studentathletes' satisfaction with academic services within athletics departments. Additionally, we examined the relationship between student-athletes' satisfaction and academic performance (i.e., GPA). A total of 226 NCAA Division I studentathletes from a Midwestern university competing in a mid-major conference participated. A survey consisting of 22 questions was created to assess the satisfaction of the four major factors (facilities, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
2
17
0
2
Order By: Relevance
“…Also, environment plays a crucial role when evaluating academic services. This supports the same findings from a previous study (Hazzaa et al, 2018). Having freshmen student-athletes evaluate their perception of the offered academic services to significantly influence their overall satisfaction demonstrates the importance of having services available.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, environment plays a crucial role when evaluating academic services. This supports the same findings from a previous study (Hazzaa et al, 2018). Having freshmen student-athletes evaluate their perception of the offered academic services to significantly influence their overall satisfaction demonstrates the importance of having services available.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, examining the perceptions of student-athletes regarding athletic academic centers found feelings of isolation and preference of relying on an academic advisor for their academic goals instead of an athletic advisor (Bell, 2009;Huml et al, 2014). Another study found varying satisfaction levels amongst class levels, demonstrating freshmen student-athletes indicate lower satisfaction levels compared to upper classmen (Hazzaa, Sonkeng, & Yoh, 2018). While these studies explored satisfaction with the quality of academic services functions, there is a gap in research in terms of how these perceptions influence other areas of the student-athlete's college experience.…”
mentioning
confidence: 99%
“…Other benefits of participation in Varsity Sports and Cup competitions as perceived by the students included completing their studies in record time and making their families proud. Given that most student-athletes do not achieve the goal of becoming professionals, they need to maximize any available opportunities related to educational and personal development (17). The student-athletes also reported that the 60-credit rule introduced by the management of the Varsity Sports and Cup competitions assisted them in completing their studies as scheduled.…”
Section: Discussionmentioning
confidence: 99%
“…In general, student-athletes interact more with athletic advisors than academic advisors because athletic departments offer specialized academic services housed in athletic facilities to keep athletes eligible and academically retained (Friedman, 2008;Hazzaa et al, 2018;Huml et al, 2014;Otto et al, 2019;Wolverton, 2008). Consequently, athletes in these facilities are often isolated from the general student body (Huml et al, 2014;Rubin & Moses, 2017); this peer environment reinforces student-athletes' reliance on athletic advisors over academic advisors.…”
Section: Conceptual Frameworkmentioning
confidence: 99%